The Effectiveness of Red Spinach Consumption, Lavender Aromatherapy, and Oxytocin Massage on Increasing Breast Milk Production Among Breastfeeding Mothers At Pmb Ulva Aliah Sahidah In 2025 - Abela Mayunita; Lina Isika (Universitas Pahlawan Tuanku Tambusai, 2026)
Background : Breast milk is a natural fluid produced by the mother’s mammary glands and serves as the primary source of nutrition for infants, containing complete nutrients and antibodies to enhance the baby’s immune system. Breast milk plays an important role in supporting optimal growth and development of infants. However, many breastfeeding mothers still experience insufficient or non-smooth breast milk production. Various non-pharmacological efforts can be implemented to increase breast milk production, including the consumption of red spinach which is rich in iron and essential nutrients, the use of lavender aromatherapy to promote relaxation, and oxytocin massage which stimulates the release of the oxytocin hormone to facilitate milk flow. The combination of these three methods is expected to improve breast milk production in breastfeeding mothers. Purpose of Writing : This study aimed to determine the effectiveness of red spinach consumption, lavender aromatherapy, and oxytocin massage on increasing breast milk production among breastfeeding mothers at PMB Ulva Aliah Sahidah in 2025. Research Methods : This study employed a quasi-experimental design with a pretest-posttest approach. The sample consisted of 50 breastfeeding mothers selected using a specific sampling technique. The interventions included regular consumption of red spinach, application of lavender aromatherapy to induce relaxation, and oxytocin massage performed according to standard procedures. Breast milk production was measured before and after the interventions using an observation sheet. The collected data were analyzed using statistical tests to determine differences in breast milk production before and after the intervention. Research Results : The results showed an increase in breast milk production after the administration of red spinach, lavender aromatherapy, and oxytocin massage. Before the intervention, most mothers experienced low or insufficient milk production, while after the intervention, most mothers showed smooth and increased milk production. Statistical analysis indicated a significant difference in breast milk production before and after the intervention. Conclusions and Recommendations : The provision of red spinach, lavender aromatherapy, and oxytocin massage was proven to be effective in increasing breast milk production among breastfeeding mothers. It is recommended that healthcare providers implement this combination of interventions as supportive non-pharmacological methods to enhance breast milk flow. Future research is suggested to involve larger sample sizes and explore additional factors influencing breast milk production.